ChemInform Abstract: Chiral Molecular Tweezers: Synthesis and Reactivity in Asymmetric Hydrogenation. Issue 35 (September 2015) - Lindqvist, Markus; Borre, Katja; Axenov, Kirill; Kotai, Bianka; Nieger, Martin; Leskelae, Markku; Papai, Imre; Repo, Timo
Abstract A new 1, 1′‐binaphthyl aminoborane is synthesized and shows exceptional catalytical activity in asymmetric hydrogenation of unhindered imines and enamines with up to 99% ee.